Answers

2014-10-15T23:42:04+08:00
Using elimination method you'll have:
x + 5y = 7   ----equation 1
-x + 2y = 0  ---equation 2
adding equations 1 and 2 you'll have
     x + 5y = 7
+  -x + 2y = 0
          7y = 7
           y = 1
multiplying equation 1 by 2 and equation 2 by 5 you'll have:
(x + 5y = 7) x 2   => 2x + 10y = 14  ----equation 3
(-x + 2y = 0) x 5  => -5x + 10y = 0   ----equation 4
subtracting equation 4 from equation 3 you'll have:
   2x + 10y = 14
-  -5x + 10y = 0
  7x + 0y = 14
    7x = 14
     x = 2
0